MENELUSURI KAJIAN PSIKOLOGI KOMUNIKASI: URGENSI DALAM BINGKAI PENDIDIKAN - Suyono (Nusantara Hasana Journal, 2024)
An educator can use communication psychology as a tool to identify the characteristics of their students. An educator who understands the characteristics of his students can certainly use an approach that is in accordance with the psychology of his students. Therefore, educational communication psychology is an important component in determining the level of student success in learning. The purpose of this study is to examine the importance of communication psychology from an educational perspective. The type of data used in this research is secondary data, and a literature approach is used as a type of qualitative research. Data was collected through documentation from various books, journals, and research reports. The research findings show that communication psychology plays an important role in education. By using communication psychology, teachers can use learning strategies that suit the psychology of students to help them understand each student's characteristics. Communication psychology can also help better communication with others in the classroom. In addition, addressing various problems that arise in the field of education, such as bullying and violence, can include the use of communication psychology. This is corroborated by many studies and literatures that discuss the importance of communication psychology to create a harmonious educational environment and improve learning outcomes.